Obesity, Heart Failure, and Obesity Paradox - Nikoo Hamzeh; Fatemeh Ghadimi; Rojin Farzaneh; Seyed Kianoosh Hosseini (Journal of Tehran University Heart Center, 2017)
The incidence and prevalence of obesity are fast increasing worldwide. Various indices have been used to measure and assess obesity. The body mass index (BMI) is the most common and practical of these indices. Overweight and obesity exert considerable adverse effects on the cardiovascular system. These effects are mediated through various neurohormonal and cytokine pathways, most of which are inflammatory mediators. Systolic and / or diastolic heart failure is more prevalent among obese and overweight individuals than among normal weight people. The concept of the “obesity paradox” has been proposed by some previously published studies, in which the prognosis of obese patients with established cardiovascular diseases, especially heart failure, is better than that of their leaner counterparts. In this review, we discuss the obesity paradox and its possible pathophysiologic mechanisms.